1996
DOI: 10.1111/j.1432-1033.1996.0143q.x
|View full text |Cite
|
Sign up to set email alerts
|

Guanine‐Rich Oligonucleotides Targeted to a Critical R · Y Site Located in the Ki‐ras Promoter

Abstract: The promoter of the murine JS-rus proto-oncogene contains a (C+G)-rich homopurine . homopyrimidine (R . Y) sequence that is essential for transcription activity. We have designed two G-rich oligonucleotides, d(TGGGTGGGTGGTTGGGTGGG) (20GT) and d(AGGGAGGGAGGAAGGGAGGG) (20AG), that have the potential to bind the critical Ki-rus sequence via tripIex-helix formation. Band-shift experiments have shown that 20GT binds the Ki-rus R . Y duplex with a AG value of -40 -t 5 kJ/mol, while 20AG appeared to have a lower affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 57 publications
(31 reference statements)
1
17
0
Order By: Relevance
“…Our results are in agreement with previously published results on purine-motif triplexes (Xodo 1995;Alunni-Fabbroni et al 1996;Arimondo et al 1998;Raghavan et al 2005). …”
Section: Circular Dichroism Studiessupporting
confidence: 83%
“…Our results are in agreement with previously published results on purine-motif triplexes (Xodo 1995;Alunni-Fabbroni et al 1996;Arimondo et al 1998;Raghavan et al 2005). …”
Section: Circular Dichroism Studiessupporting
confidence: 83%
“…In a previous work, we found that at room temperature 20AG exhibited a weaker affinity than 20GT for the c-Ki- ras target because of its strong self-association property (Alunni-Fabbroni et al, 1996). In this study, we show that the capacity of the (A,G) oligonucleotides 20AG and 30AG to bind the c-Ki-ras target is surprisingly enhanced in the temperature range of 37-65°C.…”
Section: Discussionmentioning
confidence: 74%
“…Through band-shift analyses carried out at 25°C, these authors have shown that the affinity for the human c-Ki-ras promoter of 22-mer TFOs was approximately (0.2-0.5) × 10 6 M -1 . Moreover, other K a values determined under different experimental conditions (different T and MgCl 2 concentrations) have been reported in the literature for G-rich triplex-forming oligonucleotides, varying from 10 6 to 10 8 M -1 (Durland et al, 1991;McShan et al, 1992;Vasquez et al, 1995;Noonberg et al, 1995;Olivas & Maher, 1995a,b;Xodo, 1995;Alunni-Fabbroni et al, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…In this DNA motif, each purine contains a bidentate acceptor–donor hydrogen‐bond system that can be recognized by a third guanine‐rich oligonucleotide (ODN), through the formation of G·G·C and A·A·T or T·A·T base triplets. The resulting triple‐stranded complex is thermodynamically stable under physiological or near‐physiological conditions [2–11]. As triplex‐forming ODNs bind to poly(R·Y) targets in a highly sequence‐specific manner, they represent an interesting class of DNA ligands that allow a number of applications in biotechnology and pharmacology.…”
mentioning
confidence: 99%